Penegakan Hukum Pidana dalam Perkara Pelanggaran Pedagang Kaki Lima di Kota Surabaya - Rizky Ardian Pratama; Yana Indawati (CV Rewang Rencang, 2025)
Law enforcement against street vendors who conduct trading activities in public facilities in Surabaya City is the implementation of Surabaya City Regional Regulation Number 2 of 2020. Although the regulation has regulated prohibitions and criminal sanctions, the level of violations remains high due to economic factors, lack of legal awareness, and weak effectiveness of supervision. Surabaya City Satpol PP carries out law enforcement in stages by prioritizing the principle of legality and a humanist approach. This research confirms the urgency of optimizing regulations, increasing socialization, and providing alternative solutions in order to realize a balance between the interests of public order and the protection of people's economic rights